Implementasi E-Government pada Website Bursa Kerja Online di Dinas Tenaga Kerja dan Sertifikasi Kompetensi Kota Denpasar - Isnaini, Anjar Aulia; Sastra Wijaya, Komang Adi; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
The background of the research is Presidential Instruction No. 3 of 2003 which requires all government agencies to implement E-government. The Denpasar City Manpower and Competency Certification Office implement an online job fair E-government website. The purpose of this research is to look at the implementation and obstacles in implementing the Denpasar City online job fair website using six key indicators for the success of policy implementation. The results of this study indicate that the implementation of E-government can be said to run quite smoothly. This can be seen from the six indicators used, namely bureaucratic compliance, smooth routines and no problems, performance, support, capacity have been running well, but values ??have not been fully run optimally. It can be seen from the graph in 2017 and the lack of website updates so that website visitors decrease and make the implementation of E-government less than optimal.